Newer vs. older CAD/CAM burs: Influence of bur experience on the fatigue behavior of adhesively cemented simplified lithium-disilicate glass-ceramic restorations - Schmitt de Andrade, Guilherme [UNESP]; Diniz, Vandeberg [UNESP]; Datte, Carlos Eduardo [UNESP]; Pereira, Gabriel Kalil Rocha; Venturini, Andressa Borin; Campos, Tiago Moreira Bastos; Amaral, Marina; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe; Marques de Melo, Renata [UNESP] (Elsevier, 2019)
This study evaluated the effect of the CAD/CAM burs experience (newer vs older as consequence of the milling sequence) on fatigue failure load (FFL), number of cycles for failure (CFF), and survival rates of lithium disilicate glass-ceramic simplified restorations adhesively cemented to a dentin analogue substrate. Three sets of CAD/CAM burs were used to mill disc-shaped ceramic specimens (1 bur set – 18 milled discs with 10 mm diameter and 1.5 mm thickness), considering the bur experience as a result of the milling sequence to compose the study groups: G1-6 – discs obtained from the 1st to 6th milling of each bur set; G7-12 – specimens from the 7th to 12th milling; G13-18 – discs from the 13th to 18th. Discs of dentin analogue (G10, 10 mm diameter and 2.0 mm thickness) were made to serve as substrate (base material) and randomly assigned into pairs with the respective ceramic discs. Then, the ceramic discs were adhesively cemented onto the dentin analogue substrate, composing a three-layer specimen that mimics a monolithic restoration of a posterior tooth. Specimens were tested under stepwise fatigue approach: frequency = 20 Hz, 5000 cycles at maximum load of 400 N to accommodate the testing assembly, followed by incremental steps of 200 N with initial load ranging from 10 to 1000 N, to a maximum of 20,000 cycles/each step, until the occurrence of failure (radial crack). FFL and CFF were recorded at the end of the testing and subjected to statistical analysis. Supplementary roughness analysis of the milled surface was performed (n = 18) using a contact profilometer. Residual stress after milling and acid etching were accessed via X-ray Diffractometry analysis. FFL and CFF were not affected by increase on bur experience (no statistical differences among groups), despite that, it affected both Ra and Rz parameters (G1-6 had the smoothest surface). The residual stress concentration was negligible (milling did not induce residual stress concentration). It is concluded that the fatigue behavior of adhesively cemented lithium-disilicate glass-ceramic restorations was not influenced by CAD/CAM bur experience (newer vs older as consequence of the milling sequence), and so the residual stress concentration induced by milling was negligible.
Keywords: All-ceramic; Cementation; Fatigue; Machining; Radial crack; Roughness